Ureteric Endometriosis: a 39 Years Old Lady Presented with Cyclical Lower Abdominal Pain - Hasan, Md Naheed; Akter, Mithila; Islam, Md Nazrul; Chowdhury, Md Nizamuddin; Anowar, Tanim; Ahmed, Parvez Iftekhar (Journal of Dhaka Medical College, 2018)
Abstract not available J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 98-101